2014
DOI: 10.21273/jashs.139.3.247
|View full text |Cite
|
Sign up to set email alerts
|

Fine Mapping a Clubroot Resistance Locus in Chinese Cabbage

Abstract: There are various clubroot pathogen (Plasmodiophora brassicae) resistance genes within Brassica species with european turnip (B. rapa ssp. rapifera) being identified as potentially the best source of resistance for the development of clubroot-resistant cultivars in chinese cabbage (B. rapa ssp. pekinensis). To use clubroot resistance genes eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 18 publications
0
19
1
Order By: Relevance
“…The QTLs PbBa3.1, 3.2 and 3.3 from ECD 04 conferred resistance to pathotypes 2, 10 and 7, respectively (Chen et al ., ). A CR locus (Gao et al ., ) that conferred resistance to a field isolate from Edmonton, Canada, originated from a Chinese cabbage commercial hybrid; however, the resistance of most Chinese cabbage inbred lines originated from turnip (Zhang et al ., ), so it was predicted that this CR locus was also from turnip. In B. napus , QTLs conferring resistance to isolates 01:60, k, 01.07 and 1 were mapped to chromosome N3 (Werner et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The QTLs PbBa3.1, 3.2 and 3.3 from ECD 04 conferred resistance to pathotypes 2, 10 and 7, respectively (Chen et al ., ). A CR locus (Gao et al ., ) that conferred resistance to a field isolate from Edmonton, Canada, originated from a Chinese cabbage commercial hybrid; however, the resistance of most Chinese cabbage inbred lines originated from turnip (Zhang et al ., ), so it was predicted that this CR locus was also from turnip. In B. napus , QTLs conferring resistance to isolates 01:60, k, 01.07 and 1 were mapped to chromosome N3 (Werner et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The CR locus found in this study is CRa or a CRa‐ linked gene, which could also be aligned to Arabidopsis chromosome 4. Another CR locus confers resistance to a field isolate from Edmonton and was also mapped to the same area at the bottom of N3 (Gao et al ., ), suggesting that they are linked. However, the resistant parent 12‐3 is highly resistant to pathotypes 2, 3, 5, 6 and 8, suggesting a different resistance spectrum from that of CRa , CRb , CRb kato , RCr1 or the CR locus aligned to Arabidopsis chromosome 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BC1 population showed ample variation for stem swelling trait, and the segregation pattern fits well to a normal continuous distribution which was suitable for a QTL study (Table 1, Supplementary figure 1, Supplementary figure 2). It can be noted that BC1 populations have been used in previously reported genetic analyses for the fine mapping of the club root resistance QTL in Chinese cabbage (Gao et al 2014) and the fine mapping of a major locus controlling plant height in B. napus (Wang et al 2016). Lou et al (2007) also identified QTLs for tuberous root formation using BC1 population in turnip.…”
Section: Quantitative Control Of the Stem Swelling Traitmentioning
confidence: 99%
“…Numerous studies have aimed to improve CR in Chinese cabbage, turnip, rapeseed and lettuce by introgression breeding combined with MAS (Diederichsen and Sacristan 1996, Piao et al 2007, Kutcher et al 2010, Tomita et al 2013, Gao et al 2014, Zhang et al 2015; however, few studies have focused on pak choi. In this study, we aimed to (i) analyse the inheritance of CR in pak choi and develop sequence-characterized amplified region (SCAR) markers that can practically distinguish clubroot-resistant genotypes from susceptible genotypes in a large number of individuals and (ii) improve resistance of pak choi to clubroot by introgression of the CR gene from Chinese cabbage using MAS.…”
mentioning
confidence: 99%